Sweeping the Floor or Putting a Man on the Moon: How to Define and Measure Meaningful Work - Both-Nwabuwe, Jitske M. C.; Dijkstra, Maria T. M.; Beersma, Bianca (Frontiers in Psychology, 2017)
Meaningful work is integral to well-being and a flourishing life. The construct of "meaningful work" is, however, consistently affected by conceptual ambiguity. Although there is substantial support for arguments to maintain the status of conceptual ambiguity, we make a case for the benefits of having consensus on a definition and scale of meaningful work. The objective of this article, therefore, was twofold. Firstly, we wanted to develop a more integrative definition of meaningful work. Secondly, we wanted to establish a corresponding operationalization. We reviewed the literature on the existing definitions of meaningful work and the scales designed to measure it. We found 14 definitions of meaningful work. Based on these definitions, we identified four categories of definitions, which led us to provide an integrative and comprehensive definition of meaningful work. We identified two validated scales that were partly aligned with the proposed definition. Based on our review, we conclude that scholars in this field should coalesce rather than diverge their efforts to conceptualize and measure meaningful work.